The 14th General Election has significantly changed Malaysia when Barisan Nasional suffered its first ever defeat since Independence. However, among the Malay majority, there was a growing sense of political anxiety and uneasiness as a result of the perceived loss of power, and to some extent, the erosion of national identity. In response, the nationalists and the Islamists have regrouped and reunited. This is manifested with the formal alliance of the two largest Malay-based parties, UMNO and P - Mohamed Salleh, Shahnon; Sualman, Ismail (Jurnal Ceteris Paribus, 2024)
The 14th General Election has significantly changed Malaysia when Barisan Nasional suffered its first ever defeat since Independence. However, among the Malay majority, there was a growing sense of political anxiety and uneasiness as a result of the perceived loss of power, and to some extent, the erosion of national identity. In response, the nationalists and the Islamists have regrouped and reunited. This is manifested with the formal alliance of the two largest Malay-based parties, UMNO and PAS. Amidst the backdrop of this new political realignment, social media played an important role in setting the narrative, and mobilising the masses. Therefore, working from within this background, this paper analysed the discourse of the new Malay nationalism on social media by employing a social media tool, SeoTools, to analyse the Twitter data. The findings revealed a new insight into the dynamics of the Malay mind and motivation from the context of politics, religion, and economy. There was a significant correlation between popular sentiment and social media discourse, in that there was a renewed resurgence to reassert traditional values and identity. The failure to rein in the emotion, and the expectation, eventually cause the fall of Pakatan Harapan in 2020.